Environmental science : a global concern - Cunningham, William P.; Saigo, Barbara Woodworth (Boston : McGraw-Hill, 2001)
Environment Management
Keywords: Environmental sciences; Global environment; Ecology; Population; Economics; Environmental health; Biological resources; Physical resources